PENGEMBANGAN E-MODUL GEOMETRI BANGUN DATAR MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME DI SEKOLAH DASAR - Akhromah, Rinda Hidayati; Putra, Zetra Hainul; Syahrilfuddin, Syahrilfuddin (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2024)
This research aims to develop an e-module for flat shape geometry using a constructivist approach on the topic of area and perimeter of flat shapes. The method used is research and development (R&D) based on the ADDIE model. The data collection techniques used by researchers were observation, interviews, and questionnaires. Feasibility of teaching materials by conducting validity tests and practicality tests. The validity test was carried out by three experts, namely material experts, language experts and media experts. The practicality of teaching materials was obtained through a practicality test carried out with two teachers, three individual students (one-to-one), and ten small group students (small group test). The results obtained from experts show that the teaching materials developed received a validity value with an average percentage of 0.95 (very valid). The teachers and students also gave a positive response to the practicality of the e-module, given a score by the teacher, the overall average percentage was 97.5% (very practical), three individual students (one-to-one) obtained an average percentage of 97.5% (very practical). The overall average was 93.89% (very practical), and ten small group students obtained an overall average percentage of 96.33% (very practical). So that the teaching materials produced in the form of flat shape geometry e-modules using a constructivist approach in elementary schools meet valid and practical criteria, so they are suitable for use in the mathematics learning process.